Evaluation of the correlation of MACC1, CD44, Twist1, and KiSS-1 in the metastasis and prognosis for colon carcinoma - Bo Zhu; Yichao Wang; Xiaolin Wang; Shiwu Wu; Lei Zhou; Xiaomeng Gong; Wenqing Song; Danna Wang (BMC, 2018)
Abstract Background Metastasis-associated in colon cancer 1 (MACC1) has been reported to promote tumor cell invasion and metastasis. Cancer stem cells and epithelial-mesenchymal transition (EMT) have also been reported to promote tumor cell proliferation, invasion, and metastasis. KiSS-1, a known suppressor of metastasis, has been reported to be down-regulated in various tumors. However, the associations of MACC1, CD44, Twist1, and KiSS-1 in colonic adenocarcinoma (CAC) invasion and metastasis remain unclear. The purpose of this study is to investigate the roles of MACC1, CD44, Twist1, and KiSS-1 in CAC invasion and metastasis and their associations with each other and with the clinicopathological characteristics of CAC patients. Methods Immunohistochemistry and multivariate analysis were carried out to explore the expression of MACC1, CD44, Twist1, and KiSS-1 in 212 whole-CAC-tissue specimens and the corresponding normal colon mucosa tissues. Demographic, clinicopathological, and follow-up data were also collected. Results The results of this study showed MACC1, CD44, and Twist1 expression to be up-regulated, and KiSS-1 expression was down-regulated in CAC tissues. Positive expression of MACC1, CD44, and Twist1 was found to be positively correlated with invasion, tumor grades, and lymph- node-metastasis (LNM) stages and tumor-node-metastasis (TNM) stages for patients with CAC. Positive expression of KiSS-1 was inversely associated with invasion, tumor size, LNM stage, and TNM stage. The KiSS-1-positive expression group had significantly more favorable OS than did the KiSS-1-negative group. Univariate analysis indicated that overexpression of MACC1, CD44, and Twists1 was negatively associated with longer overall survival (OS) time, and there was a positive relationship between KiSS-1-positive expression and OS time for patients with CAC. Multivariate Cox analysis demonstrated that overexpression of MACC1, CD44, Twist1, and low expression of KiSS-1 and LNM and TNM stages were independent predictors of prognosis in patients with CAC. Conclusions The results in this study indicated that levels of expression of MACC1, CD44, Twist1, and KiSS-1 are related to the duration of OS in patients with CAC. MACC1, CD44, Twist1, and KiSS-1 may be suitable for use as biomarkers and therapeutic targets in CAC.